Iconographic Analysis of the Front of the Temple of the Holy Kings of Metztitlán, Hidalgo - Moreno Vidal, Carmen Fabiola (Eikón / Imago, 2018)
The facade of the Metztitlán temple, has a rich decoration based on plant and animal elements, both of them with a strong symbolic load and a message aimed at exalting the glory of Christ and the spiritual relationship with the joys of eternal life through baptism, in the decoration the evangelizing thought of the Augustinian order is also reflected, which was the first to establish itself in the Sierra Alta de Hidalgo. This facade also presents in its decoration several symbols belonging to the indigenous world and which are related to the stars, whose position in the firmament governed their rituality, so it was important to place them in a veiled form and as part decoration in important areas of the façade. In this article we have tried to make an analysis of the symbolism of the main elements that make up the facade, both of the elements that belong to the Christian world, as to the indigenous, and that managed to integrate and complement each other, being able to transmit a comprehensible message for both evangelizers and evangelized.